Written repetition vs. oral repetition: Which is more conducive to L2 vocabulary learning?. (31st August 2018) - Candry, Sarah; Deconinck, Julie; Eyckmans, June
Structural elaboration, i.e. increased attention to word-form, can aid an L2 learner in retrieving the form of a newly learned word (Barcroft, 2002 ), which is crucial for language production. However, the possibilities for developing meaningful interactions with the form of new words are rather limited. Previous research has proposed word writing as a structural elaboration technique (e.g.Candry, Elgort, Deconinck, & Eyckmans, 2017 ;Eyckmans, Stengers, & Deconinck, 2017 ) and has demonstrated that word writing promotes L2 word-form retrieval as compared to a semantically elaborative condition (Candry et al., 2017 ;Elgort, Candry, Boutorwick, Eyckmans, & Brysbaert, 2016 ). The advantage of word writing with reference to other structurally elaborative conditions has not been investigated yet. Therefore, the present study compared a written repetition condition with a condition in which learners said the new L2 vocabulary out loud repeatedly. 67 Dutch-speaking learners of German learned 24 unknown German words in one of these two conditions or a control condition. Both immediate and delayed measures of word knowledge were administered. The results showed that immediate form recall is marginally better when words are learned through written repetition than through oral repetition, though this advantage disappeared after one week. When it comes to meaning recall and implicit word knowledge, no differences between the two conditions were observed.